Reparación de tejidos perirradiculares en el tratamiento endodóntico no quirúrgico. Una revisión - Castillo Páez, José Alberto (2024)
Introduction: Non-surgical endodontic treatment aims to prevent apical periodontitis, achieved with the disinfection of the root canal system. Additionally, there are pathologies where the toxic content of the canal goes to the periradicular tissues, causing osteolysis or lesions of the bone tissue that are radiographically observed as radiolucent images. When the endodontic treatment is successful, the repair of these lesions occurs over time. Aim: To analyze the periradicular repair process of non-surgical endodontic treatment and the factors that affect it. Materials and Methods: An electronic search was carried out using the search engines PUBMED, Scopus, Google Academic, and Scielo with the words “Non-Surgical Endodontic Treatment,” “Periapical Tissues,” “Biological Repair,” “Apical Repair.” Factors such as incomplete texts, PDF texts, and publication date of the article were considered, including data from the last five (05) years. Results: The information reviewed comprised 236 articles analyzed with the inclusion and exclusion criteria, and only 42 articles met these criteria. Conclusion: The success of endodontic treatment lies in the absence of clinical and radiographic signs and symptoms of infection; this is achieved with a good application of clinical protocols and procedures focused on the disinfection of the root canal system, from diagnosis, biomechanical preparation, and disinfection of the root canal system with irrigating substances and filling, including coronal rehabilitation from an aesthetic and/or prosthetic point of view.